Prevalence of Hypertension, Its Risk Factors and 10-year Cardiovascular Disease Risk among Bank Employees in Lagos State, Nigeria - Omobola Yetunde Ojo; Tolulope Olasehinde; Adeyinka Adeniran; Chisom Florence Chieme; Adedayo Ayodele Aderibigbe (Nigerian Postgraduate Medical Journal, 2024)
Background: Hypertension is a significant global public health concern, with unique risk factors affecting those in the banking sector due to their work environment. This study aimed to determine the prevalence of hypertension among bank employees and identify specific contributing risk factors. Materials and Methods: A cross-sectional survey of 250 bank employees used pretested structured questionnaires. Various measurements, including body mass index (BMI), blood pressure, lipid profile parameters and cardiovascular events, were recorded. Data were analysed using SPSS software. Categorical variables are presented as frequencies and percentages. Binary logistic regression was employed to identify independent predictors of hypertension (P < 0.05). Results: The study participants had a mean age of 37.56 ± 8.98, with 54.5% being female. The majority (98.8%) had tertiary education, and 94.7% resided in urban areas. The prevalence of hypertension was 33.3%. Higher BMI is significantly associated with increased odds of hypertension. For each unit increase in BMI, the odds of having hypertension are approximately 1.98 times higher. Hypertension was also significantly more prevalent in those participants with prior hypertension diagnosis, those with a family history of hypertension, smokers and those who added salt to their food on the table (P < 0.05). Conclusion: The alarmingly high prevalence of hypertension underscores the need for targeted intervention and health promotion initiatives. With recognised risk factors, emphasis must be placed on the importance of lifestyle modifications and workplace wellness programmes to mitigate the burden of hypertension.